Evaluasi nutrisi campuran onggok dan ampas tahu terfermentasi Aspergillus niger, Rizhopus oligosporus dan kombinasi sebagai bahan pakan pengganti tepung jagung - Yohanista, Maria; Sofjan, Osfar; Widodo, Eko (Faculty of Animal Science, Universitas Brawijaya, 2014)
The purpose of this study was to evaluate the nutritional value of cassava and tofu mixture fermented by Aspergillus niger, Rizhopus oligosporus and the combination among them (50% of Aspergillus niger and 50% of Oligosporus Rizhopus) as a substitute feed ingredients corn meal. The research method was laboratory experiment using the analysis of completely randomized design (CRD) factorial (3 x 4). The first factor was the 3 types of microbes (M) that consisted of M0 = fermentation by Aspergillus niger, M1 = fermentation with Rhizopus oligosporus and M2 = fermentation with the combination 50% of Aspergillus niger and 50% of Rhizopus oligosporus. The second factor was 4 incubation time (T) that consisted of T0 = non-fermented, T1 = 2 days of incubation time, T2 = 4 days of incubation time and T3 = 6 days of incubation time. Each treatment was repeated 3 times. Variables measured were proximate nutrient content, fiber component content (NDF and ADF, silica, lignin), soluble protein content and mineral content (calcium and phosphorus). Data were analyzed by ANOVA, if there were differences among the treatments then it woukd be followed by Duncan's Multiple Range Test. Results showed that microbes provided a significant influence (P <0.01) on ash (%), crude protein (%), crude fiber (%), crude fat (%), gross energy (Kcal / Kg), soluble protein (%), NDF (%), ADF (%), cellulose (%), hemicelluloses (%) and silicate (%) but they did not provide significant effect on lignin (%). The incubation period had highly significant effect (P <0.01) on ash (%), crude protein (%), crude fiber (%), crude fat (%), gross energy (Kcal / Kg), soluble protein (%), NDF (%), ADF (%), cellulose (%), hemicelluloses (%), lignin (%) and silicate (%). It was concluded that fermentation was best treated using a combination between 50% of Aspergillus niger and 50% of Rhizopus oligosporus with 2 days of incubation time. The study suggested for further research (biological test) to use a mixture of cassava and fermented tofu as a substitute feed ingredients corn meal in broiler chickens. Keywords: Cassava waste, tofu waste, fermentation, Aspergillus niger, Rizhopus oligosporus and corn meal